2021
DOI: 10.1242/dmm.048934
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming in cancer: mechanistic insights from Drosophila

Abstract: Cancer cells constantly reprogram their metabolism as the disease progresses. However, our understanding of the metabolic complexity of cancer remains incomplete. Extensive research in the fruit fly Drosophila has established numerous tumor models ranging from hyperplasia to neoplasia. These fly tumor models exhibit a broad range of metabolic profiles and varying nutrient sensitivity. Genetic studies show that fly tumors can use various alternative strategies, such as feedback circuits and nutrient-sensing mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 167 publications
(269 reference statements)
1
7
0
Order By: Relevance
“…Imaginal discs. Ldh expression has been extensively studied in the larval imaginal discs [26,[36][37][38][39][40]. These studies have consistently observed relatively low levels of Ldh expression during normal imaginal disc development.…”
Section: Fat Body and Salivary Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaginal discs. Ldh expression has been extensively studied in the larval imaginal discs [26,[36][37][38][39][40]. These studies have consistently observed relatively low levels of Ldh expression during normal imaginal disc development.…”
Section: Fat Body and Salivary Glandsmentioning
confidence: 99%
“…Similarly, studies of Drosophila disease models have also begun to focus on the link between lactate metabolism activity and tumor growth [for review, see 26], neuronal health and aging [27][28][29][30][31][32][33][34], as well as during infections and immune challenges [35]. Notable among these findings is that Drosophila tumors up-regulate Ldh in a manner that mimics the elevated Ldh-A activity observed in many human cancer cells [26,[36][37][38][39][40], indicating that Ldh in both flies and humans serves a beneficial role in tumorous growth. Thus, studies of Drosophila Ldh hold the potential to better understand how mammalian Ldh homologs function in development and disease.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, metabolites and metabolic pathways in flies and mammals are highly conserved. Therefore, many established tools for studying metabolic changes in mammals can be directly applied to fly studies ( 156 ). So far, there exist a variety of tools established to directly measure intracellular ROS.…”
Section: Cancer Metabolism Revealed By Fly Studiesmentioning
confidence: 99%
“…For example, dihydroethidium (DHE) is one of the most frequently used dyes which fluoresces upon oxidation by superoxide ( 157 ). In addition, MitoSOX is used to distinguish the sources of ROS as a modified version of DHE with a mitochondrion-targeting group to observe ROS that mitochondria generate ( 156 , 158 ). Another widely used fluorogenic probe for oxidative stress in mammals is 2′,7′-Dichlorofluorescin diacetate (DCFH-DA) probe, which also proved efficient in flies ( 153 , 155 , 159 , 160 ).…”
Section: Cancer Metabolism Revealed By Fly Studiesmentioning
confidence: 99%
“…There has also been concentrated focus on the roles metabolism and insulin signalling have in cancer, as diabetes and obesity are prominent risk factors for cancer. In their recent review, Lam Wong and Verheyen (2021) explain how tumour survival, growth and metastasis are promoted by dysregulated insulin signalling and insulin receptor expression in Drosophila models of T2D. It was suggested that components of the insulin signalling pathway present in the circulation act as biomarkers for certain cancers.…”
mentioning
confidence: 99%